Quality measures for dental care: a systematic review - Righolt, Amy; Listl, Stefan (Community dentistry and oral epidemiology, 2019)
Objectives This systematic review aimed to (a) provide an overview of existing quality measures in the field of oral health care, and to (b) evaluate the scientific soundness and applicability of these quality measures. Methods A systematic search was conducted in three electronic databases MEDLINE (via PubMed), EMBASE (via OVID) and LILACS (via BIREME). The search was restricted to articles published between 2002 and 2018. Publications reporting on the development process or clinimetric properties of oral health care quality measures for outpatient oral health care in dental practices were included. The identified publications reporting on oral health care quality measures were critically appraised with the Appraisal of Indicators through Research and Evaluation 2.0 (AIRE 2.0) instrument to evaluate the soundness and applicability of the measures. Results The search strategy resulted in 2541 unique and potentially relevant articles. In total, 24 publications were included yielding 215 quality measures. The critical appraisal showed a large variation in the quality of the included publications (AIRE scores ranging from 38 to 78 out of 80 possible points). The majority of measures (n = 71) referred to treatment and preventive services. Comparably, few measures referred to the domain patient safety (n = 3). The development process of measures often exhibited a lack of involvement of patients and dental professionals. Few projects reported on the validity (n = 2) and reliability (n = 3) of the measures. Four projects piloted the measures for implementation in practice. Conclusions This systematic review provides an overview of the status quo with respect to existing quality measures in oral health care. Potential opportunities include the piloting and testing of quality measures and the establishment of suitable information systems that allow the provision of transparent routine feedback on the quality of oral health care.
First published: 30 October 2018
Gesehen am 04.04.2019